Analisis Yuridis Asas Keseimbangan dalam Klausula Baku Aplikasi Shopee: Juridical Analysis of the Principle of Balance in the Standard Clauses of the Shopee Application - Olivia Nabila Sambas; Setiawan Wicaksono; Prawatya Ido Nurhayati (Faculty of Law, Universitas Brawijaya, 2021)
This research aims to find out the standard clauses in the Shopee application service conditions that fulfill the principle of balance in contract law. The principle of balance requires that the parties to an agreement have an equal position in having rights and carrying out obligations. However, in practice, especially the inclusion of standard clauses implemented between Shopee and traders does not fulfill the principle of balance. This is due to the unequal position between Shopee and traders where Shopee has an economic advantage which is marked by Shopee's existence as one of the largest marketplaces in Indonesia and the most sought after by traders to offer their products. On the other hand, traders are positioned as weak parties in the agreement because the take it or leave it principle applies. The clause that attracts the author's attention is the clause that states the user's submission to any additional rules that apply in the future and are determined unilaterally by Shopee. One example is Shopee's action of automatically including merchants in the Free Shipping program, where the included merchants do not necessarily want to take part in the program because there are other costs that must be incurred. These unilateral decisions then bring various material losses to traders. This type of research is normative juridical using a statutory approach method by means of literature study to collect information regarding standard clauses and the principle of balance. The data analysis used by the author is a systematic interpretation carried out by interpreting the law as a unified system. Based on the results of this research, it can be seen that the standard clauses in Shopee's terms of service do not fulfill the principle of balance both in terms of forming and implementing the agreement.